THE INFLUENCE OF TRAINING AND COMPENSATION ON EMPLOYEE PERFORMANCE IN WILD TIGER PRAWN FARMS IN TANGGAMUS - Fanni, Yo; Iskandar, Iskandar (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Human resources play a crucial role in the success of a company. Therefore, it is essential for companies to provide effective training and fair compensation to enhance employee performance and ensure the smooth functioning of the organization. The objective of this study is to examine the impact of training and compensation on employee performance in windu alam tiger prawn farm. The research sample consisted of 30 employees, and the entire population was included using Non-Probability Saturation sampling technique. Data collection was done through a questionnaire system, and the analysis was conducted using multiple linear regression with the assistance of SPSS version 25. Various tests such as validity, reliability, normality, multicollinearity, and heteroscedasticity were performed to analyze the data. The hypothesis testing included simultaneous, partial, and R2 determination coefficient tests. The findings revealed that Training (X1) has a positive influence on Employee Performance (Y), and Compensation (X2) also has a positive impact on Employee Performance (Y). Moreover, the study concluded that both Training and Compensation have a positive effect on employee performance. This research holds both theoretical and practical implications, contributing to the field of human resource management and providing valuable insights for companies in making informed decisions.